Impact of glutathione-S-transferases (GST) polymorphisms and hypermethylation of relevant genes on risk of prostate cancer biochemical recurrence: a meta-analysis. - Rui Chen (Public Library of Science (PLoS), 2013)
Introduction Accurate prediction of the biochemical recurrence (BCR) is critical for patients after intended curative therapy like radical prostatectomy (RP) or definitive radiotherapy for prostate cancer. Glutathione-S-transferases polymorphisms as well as hypermethylation of GSTP1 and functional genes in carcinogenesis, including tumor suppression gene (APC), hormone receptor that regulates cell growth and differentiation gene (RARbeta) were reported to be associated with BCR. Nevertheless, the reported results are inconsistent. To evaluate the relationship between glutathione-S-transferases polymorphisms and hypermethylation of these genes and the risk of prostate cancer BCR, we carried out a meta-analysis of the published studies. Methods and materials We performed a search in Medline, Embase and CNKI database with GST, APC, RARbeta in combination with single nucleotide polymorphism, hypermethylation, prostate cancer and recurrence. Languages were restricted to English and Chinese. Results Our study included 4 case-control studies and 7 cohort studies including 12 data sets and 3,037 prostate cancer patients. We confirmed that APC hypermethylation is associated with a modest hazard for biochemical recurrence after RP (HR = 1.85, 95%CI = 1.12-3.06). We also suggest GSTP1 polymorphism and CpG hypermethylation tested in serum are associated with BCR (HR = 1.94, 95%CI = 1.13-3.34). We also identified a possible association between GSTM1 null polymorphism and prostate cancer biochemical recurrence risk with borderline significance (HR = 1.29, 95%CI = 0.97-1.71). Conclusion To our knowledge, this is the first meta-analysis evaluating the relationship of polymorphisms and hypermethylation in GSTs and biochemical recurrence. GSTM1, GSTP1 polymorphisms and hypermethylation of GSTP1, APC may be potential biomarkers for the evaluation of the probability of BCR. Further studies are warranted to validate these findings in larger cohorts with longer follow-up.